Transcriptome Analysis of the Effects of X-Ray Radiotherapy on Non-small-cell Lung Cancer Using Next-generation Sequencing - Aras, Serhat; Koprulu, Tugba kul; Cam, Burcin Erkal; Balkan, Julide; Erdem, Esra; Cikler, Esra; Kara, Altan (INT INST ANTICANCER RESEARCH, 2025)
Background/Aim: This study investigated the acute effects of flattening filter (FF) and flattening filter-free (FFF) beams on gene expression in non-small-cell lung cancer (NSCLC). Materials and Methods: Thirty-six adult athymic nude mice were divided into five groups. The control group did not undergo any radiotherapy or treatment procedures, whereas in the lung cancer (LCa) group, a cancer model was created but not irradiated. LCa models received 20 Gy radiotherapy with FF at 400 MU/min, or with FFF at 1,000 or 1,800 MU/min dose rates. The mice were irradiated 20 days after A549 cancer cell-line implantation and sacrificed 48 h after irradiation for genetic analysis. Results: Twelve genes were identified as being common across all radiotherapy groups. The expression of most of these genes changed as the dose rate increased. Seven of these genes were also common to the LCa and control groups. Three genes down-regulated in the untreated cancer group showed increased expression with higher dose rates in treated groups. Significant differences were observed in glutamatergic synapse, actin cytoskeleton regulation, and steroid synthesis in FF-400 and FFF-1000. The FFF-1800 group exhibited significant changes in RNA transport, actin cytoskeleton regulation, and phagosome-associated pathways. Conclusion: FFF beams induced more extensive and pronounced gene-expression changes compared to FF beams in NSCLC.
Keywords: Lung cancer; radiotherapy; flattering filter; flattering filter free; RNA sequencing; next-generation sequencing; BEAMS; Research & Experimental Medicine